The Factors that Affect on Employee Performance of Cimanggis Bojonggede Bogor Urban Village Office Employees - yusyanah yusyanah (Majalah Ilmiah Bijak, 2021)
The purpose of this study was to determine the effect of motivation, discipline and work environment on the performance of the employees of the Cimanggis Bojonggede Village Office, Bogor. This research is a quantitative research. The population in this study were 32 employees of the Office of the Cimanggis Village, Bojonggede, Bogor, using nonprobability sampling analysts. The results showed that motivation and work environment partially had a significant effect on employee performance, while work discipline had no significant effect on employee performance partially. Simultaneously, motivation, discipline and work environment affect employee performance